(untitled) - Ndou, Sedzani

Evaluation of host transcriptional biomarkers in the diagnosis of TB disease and optimization of multi-colour immunophenotyping assay from the QuantiFERON® TB GOLD Plus cell sediments (2020)
Thesis (MSc)--Stellenbosch University, 2023.